Derecho al doble conforme y la garantía de aplicación del principio de favorabilidad a personas que cumplen una pena, en el cantón Guaranda– Bolívar, año 2021. - Borja Borja, Marlon Marcelo (2023)
If the Ecuadorian legal norm is analyzed, it is found that the right to double conformity is a right that has been legally established in the country, lack of application of the guarantee of double conformity, which is established in the Ecuadorian Constitution, specifically in article 76, numeral 7 literal m, besides being instituted in international regulations to which our country is subject, such as the Pact of San José of Costa Rica in its article 8 numeral 2, literal h. Therefore, the lack of application of the principle of double conformity before the issuance of a procedural norm is evident since there would be no legal process to guarantee this right and after the creation of the procedural norm that regulates this, it leads to a problem with another principle which is that of favorability since prior to these procedural norms there were multiple judicial decisions in which the exercise of the right to double conformity was not allowed. The principle of favorability is also a legal tool legally constituted in article 5 numeral, possessing constitutional character as it is provided by the supreme norm in its article 76 numeral 5, with the issuance of the procedural rules governing the application of double conformity, resolution No. 04-2022 created by the National Court of Justice, This generates a violation of the legal security of persons sentenced prior to this norm, who are fully entitled to have the principle of favorability applied to them, thus seeking the retroactive application of the norm, thus guaranteeing their right to double conformity and favorability. The core problem lies in the fact that the principle of favorability must be applied with the exception of retroactivity, since it constitutes a law that can put the sentenced persons in a beneficial or better position than the one they currently have, besides that in the particular case of the right of double conformity it falls on the guaranteeing duty of the State towards the citizens, The state having established this right in 2008 and generating the procedural norm that allows exercising this right in 2022, but by this time multiple sentences have been issued in which these people have been condemned in second instance depriving them of their right to double conformity, subsequently ignoring these people of the beneficial norm that assists them and not activating the principle of favorability. With the realization of the research project a bibliographic study was carried out where these principles are analyzed from their doctrinal bases, conceptualizations, as well as 4 the information of knowledge of judges regarding the application of these norms was compiled, it is also included the analysis of the legal consequences of inapplication of minimum principles within the criminal proceedings.